Déficit funcional do diafragma crural em obesos mórbidos com aumento da exposição ácida no esôfago - Campos, Mylena Pessoa Capistrano (2023)
Obesity leads to anatomical and functional dysfunction of the esophagogastric junction (EGJ), which can lead to gastroesophageal reflux disease (GERD). The objective of this study was to evaluate whether there is a functional deficit of the crural diaphragm (CD) in morbidly obese patients with increased acid exposure in the esophagus. Healthy and asymptomatic volunteers were selected, with BMI<30 (n=26), and obese volunteers with BMI>40 (n=21), all evaluated by 24-hour pH monitoring and esophageal manometry, through which the following metrics were evaluated: maximum inspiratory pressure (maxP), intragastric (PIG), transdiaphragmatic (Pdi), intraesophageal (PIE), the axial displacement of the diaphragm (DS), considered as the maximum lowering of the GEJ, during a respiratory maneuver, and the Pmax reached per unit of GEJ displacement (maxP/DS). Afterwards, they underwent standardized inspiratory maneuvers with progressive loads. The morbidly obese were subdivided and evaluated according to (n=7) and without (n=14) increased acid exposure (AE>4%) in the esophagus. It was found that maxP (76.8±18.5 v 56.2±19.5 p 0.0006), SGA (17.20±4.86 v 6.94±7.37 p<0.0001) and Pdi (22.62±5.33 v 17.41±10.61 p 0.00352) are higher in morbidly obese patients compared to non-obese subjects in spontaneous breathing. Under inspiratory maneuvers with loads (12, 24 and 48cmH2O): the morbidly obese had higher Pmax/DS with increasing load compared to the non-obese. Among the morbidly obese, there was no difference in age, height, presence of hiatus hernia, Pmax, SGA, Pdi and PIE. In relation to the morbidly obese without AS (n=14), they had higher maxP/DS compared to the morbidly obese with AS (5.85±1.03 v 5.26±0.64 p 0.1261; 6.00±0.98 v 5.34±0.42 p 0.0448; 5.98±0.94 v 5.35±0.41 p 0.0444) and non-obese (5.85±1.03 v 5.17± 0.97 p 0.0510; 6.00±0.98 v 5.19±0.88 p 0.0167; 5.98±0.94 v 5.32±0.87 p 0.0371). It is possible that there is a functional deficit of the crural diaphragm in morbidly obese patients, which may contribute to increased acid exposure in the esophagus.